2019
DOI: 10.1088/2515-7620/ab3b8c
|View full text |Cite
|
Sign up to set email alerts
|

Excess phosphorus from compost applications in urban gardens creates potential pollution hotspots

Abstract: Urban sustainability initiatives often encompass such goals as increasing local food production, closing nutrient loops through recycling organic waste, and reducing water pollution. However, there are potential tradeoffs among these desired outcomes that may constrain progress. For example, expansion of urban agriculture for food production may create hotspots of nutrient pollution if nutrient recycling is inefficient. We used gardener and urban farmer survey data from the Twin Cities Metropolitan Area (Minne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 44 publications
2
37
0
Order By: Relevance
“…Before the current experiment began in 2017, soil from all plots was again homogenized and redistributed. At the beginning of the current experiment, garden soil was high in organic matter (9.4%) and available P (Bray P 75 mg/kg) as a result of previous compost addition; similar to the median Bray P in urban gardens surveyed in Minneapolis and Saint Paul [17].…”
Section: Site Descriptionsupporting
confidence: 55%
See 3 more Smart Citations
“…Before the current experiment began in 2017, soil from all plots was again homogenized and redistributed. At the beginning of the current experiment, garden soil was high in organic matter (9.4%) and available P (Bray P 75 mg/kg) as a result of previous compost addition; similar to the median Bray P in urban gardens surveyed in Minneapolis and Saint Paul [17].…”
Section: Site Descriptionsupporting
confidence: 55%
“…While nutrient use efficiency has been a focus of research in rural agriculture [13,14], it has received little attention in UA. Recent observational studies of UA have found evidence of excessive application of compost-derived nutrients leading to build-up of P (and, to a lesser degree, N) in garden soils [15][16][17]. Overapplication of P likely results from the relatively low N:P ratio of many composts relative to requirements for crop growth (so that applying compost based on plant N demand results in excessive P inputs) [18], as well as the general lack of economic or regulatory disincentives against applying excess nutrients in small-scale urban agriculture [19], and a "more is better" mentality by many urban gardeners result in excessive nutrient application [17,20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The overuse of compost in rain gardens and green roofs can cause phosphorus release [236,237]. Compost is often added to improve vegetation growth and toxic metal removal but contains and is capable of leaching phosphorus [28,238].…”
Section: Potential Negative Consequencesmentioning
confidence: 99%